2013
DOI: 10.1111/are.12186
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the plant protein ratio in the diet of white shrimp,Litopenaeus vannamei(Boone), usingBacillus subtilisE20-fermented soybean meal as a replacement

Abstract: This study aimed to improve the nutritional value and utilization of soybean meal (SBM) used as feed ingredient for shrimp by an approach of solid‐state fermentation with Bacillus subtilis E20. The protein content and B. subtilis E20 proliferation significantly increased, as the initial moisture increased from 30% to 50% during fermentation. Compared with SBM, the protein content of FSBM increased by 19% after fermentation, accompanied by an increase of 18.75% in the total hydrolyzed amino acids. The free amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 39 publications
6
107
5
Order By: Relevance
“…Recently, Shiu et al . () reported that the crude protein and hydrolysed amino acid contents were significantly increased by 19% and 18.75%, respectively, in fermented soybean meal with Bacillus subtilis . In the present study, essential and non‐essential amino acids were increased after the fermentation of de‐oiled JSM.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Shiu et al . () reported that the crude protein and hydrolysed amino acid contents were significantly increased by 19% and 18.75%, respectively, in fermented soybean meal with Bacillus subtilis . In the present study, essential and non‐essential amino acids were increased after the fermentation of de‐oiled JSM.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that probiotics can improve animal health and growth performance through by improving the intestinal microbiota balance, feed quality, growth‐promoting factors, and digestive enzyme contributions, and augmenting the immune response (Shiu et al, ; Verschuere, Rombaut, Sorgeloos, & Verstraete, ; Wang et al, ). Some useful bacterial strains, such as Micrococcus , Debaryomyces , Enterococcus , Bacillus , Lactococcus , Photorhodobacterium , Lactobacillus , and Saccharomyces (De et al, ), have been added to diets or water for shrimp in the larval or juvenile stage to increase their health status and/or growth performance (Liu et al, ; Rengpipat, Phianphak, Piyatiratitivorakul, & Menasvetam, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, incorporating Bacillus into the diet can increase the feed utilization, resulting in increased growth of shrimp. The probiotic, B. subtilis E20, is able to secrete digestive enzymes such as protease (Liu et al, ) and phytase (Cheng, Chiu, Guu, Tsai, & Liu, ), which might increase shrimp growth and feed efficiency when added to the shrimp diet (Liu et al, ), and improve the nutritional utilization and value of feed ingredients after fermentation with B. subtilis E20 (Shiu et al, ). This evidence can explain why the feed utilization efficiency was improved by dietary supplementation with B. subtilis E20 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…FM inclusion level depends of protein used, for example for soy meal, the substitution reaches 37.42% whereas for fermented soy raised 61.67% of substitution (Shiu et al . ). These high protein levels in diets imply a significant increase in feed prices, and feeding is considered to represent around 50–70% of total production costs.…”
Section: Introductionmentioning
confidence: 99%